Bruges. L'Eglise de Jérusalem - Jérusalem church, GP123100 - Auteur inconnu (Wikimedia Commons)
Carte postale ancienne issue de Wikimedia Commons. Titre: Bruges. L'Eglise de Jérusalem - Jérusalem church, GP123100. Title Bruges. L'Eglise de Jérusalem - Jérusalem church Date [date de publication inconnue] Publisher Paris: Neurdein Uniform title Brugge. Gebouwen. Kerken en kapellen. Jeruzalemkerk Series Belgique. Province de Flandre occidentale. Cartes postales Belgium. Province of West-Flanders. Postcards België. Provincie West-Vlaanderen. Prentkaarten Genre Post cards Extent 1 kaart / postcard Graphic Beige Language French Additional info General note: Titelgegevens ontleend aan prentkaart Source Library Catalog Source ID lbsn9994275887001471
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale